Effective atomic number and electron density determination for fricke gel dosimeters using different methods - Ouiza Moussous (Journal of Medical Physics, 2022)
The effective atomic number and electron density of some Fricke gel dosimeters were calculated for photon interaction in the energy range from 10 keV to 1000 MeV using Auto-Zeff, direct and power law methods. The results are presented relative to those of water to allow direct comparison. It is found, that the effective atomic numbers and effective electron densities calculated with the Auto-Zeff and direct methods, demonstrates a good agreement in the energy interval extending from 0.1 MeV to 10 MeV. For effective atomic number relative to water, Ferrous Agarose Xylenol gel showed better water equivalence with difference up to 0.3%, while FX-PVA-GTA and Ferrous Xylenol Gelatin gels showed differences up to 2.26% and 2.25%, respectively.